PENGARUH PEMBERDAYAAN TERHADAP PRODUKTIVITAS PELAKU USAHA MIKRO KECIL DAN MENENGAH DI DESA JATIKALANG KECAMATAN PRAMBON SIDOARJO - suharyanto, suharyanto (Majalah Ekonomi, 2014)
Background. This research intended to assess the Organizational Personnel Empowerment to the productivity which must be performed to the entrepreneur of UMKM in Jatikalang Village Prambon Distric Sidoarjo Method. This research was conducted in Sidoarjo which covered 20 entrepreneurs as respondent. This research by utilizing Regression, the technique was processed with SPSS 18.0 to analyze some hypothesis. The intercorrelations models between two variables in this study revealed that the hypothesis have significant correlation. Conclusion. The result of this research were empirical date of the development of the theoretical of human resoureces and practice management.